Educação literária: desafios e possibilidades na formação do leitor de literatura infantil e juvenil - Santos, Cintia Gama dos (Universidade Federal do Tocantins, 2024)
This article's central theme is the challenges and methodological possibilities of teaching children's and young people's literature (LIJ). The decision to investigate this topic was sparked by the results obtained from carrying out the Supervised Internship in a state public school located in the central part of Porto Nacional. To this end, the methodological path carried out consisted of bibliographic and documentary, with a qualitative, descriptive approach. Thus, the academic relevance of this production aims to provide theoretical support for other researchers interested in the same topic, contributing to the expansion of methodological proposals aimed at formal LIJ teaching, considering the digital technological information and communication tools available, bearing in mind that We have a contemporary media society as a time frame, demonstrating the need to implement a significant literary education, above all, aimed at developing the subjects' idiosyncrasy skills and abilities from a perspective of valuing human sensitivity.